Transformasi Sakralitas dan Intimitas di Era Digital: Menimbang Pernikahan Virtual dalam Perspektif Sosio-Yuridis: The Transformation of Sacrality and Intimacy in the Digital Era: Understanding Virtual Weddings from a Socio-Legal Perspective - Ita Ma’rifatul Fauziyah; Nikmatul Azizah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
The digital age has fostered the emergence of virtual marriage, posing unprecedented legal and socio-cultural challenges. This study examines the socio-cultural implications of digital marriage and analyzes the transformation of ritual meaning in the era of mediatization. Utilizing a qualitative approach with thematic analysis and case studies from various Indonesian regions, this research evaluates how technology redefines the concepts of